Development and performance of the 20" PMT for Hyper-Kamiokande. (February 2020) - Bronner, C; Nishimura, Y; Xia, J.; Tashiro, T.
Abstract: The inner detector of the future Hyper-Kamiokande experiment will be instrumented with 40000 20" photo-multiplier tubes (PMTs). Two models of PMTs are considered: the R12860 from Hamamatsu Photonics (nominal option), and the GDB-6203 from North Night Vision Technology (alternative option). Both models show improved performances compared to the PMTs used in the currently running Super-Kamiokande experiment. We present here the measurements of the performance of the nominal and alternative option PMTs done in the context of the Hyper-Kamiokande project, as well as the first use of those new PMTs in a running experiment, and other on-going developments for their future use in the Hyper-Kamiokande detector.